Evaluation of Engraftment and Adverse Effects of Granulocyte Colony Stimulating Factor versus PEG Granulocyte Colony Stimulating Factor in Patients Undergoing Autologous Hematopoietic Stem Cell Transplantation: GCSF vs. PEG-GCS Effects on Engraftment in HSCT - Mehdizadeh, Mahshid; Tavakoli-Aradakani, Maria; Zamani, Shayan; Zamani, Gholamreza; Nikpour, Naeem (Iranian Journal of Pharmaceutical Sciences, 2021)
Hematopoietic stem cell transplantation (HSCT) is an effective treatment for many hematological malignancies. Engraftment is the foremost step in the autologous hematopoietic stem cell transplantation (AHSCT) process in which different granulocyte colony-stimulating factors with various administrations are used. In this study, we evaluated and compared the efficacy and side effects of two forms of recombinant granulocyte colony-stimulating growth factors (GCSF) ,GCSF and Peg GCSF, In this randomized clinical trial, 60 consecutive patients with multiple myeloma, Hodgkin's and non-Hodgkin's lymphoma who underwent AHSCT were included, the average age of the patients was 55; the patients were then divided into two groups so the comparison of efficacy and side effects between the two methods become achievable. The local ethical committee approved the study with the code of SB2019:210291, and the Helsinki declaration was respected across the study. In the first group, patients received peg GCSF at a dose of 6 mg on day five, and the second group received GCSF started with 5μg/kg from day 5. We compared engraftment time and adverse effects in the two groups. Our study demonstrated no difference between the two groups regarding need for transfusion and infection complications; also, the two groups did not differ in terms of the flue-like syndrome, the type of infection and the recorded number of febrile neutropenia. Mean leukocyte engraftment days were 10.97 ± 1 and 11.1 ± 1.1 that was similar in both groups (P=0.328). Mean platelet engraftment days were 11.03 ± 2.4 and 11.1 ± 2.4 without significant difference (P=0.714).it was concluded that Pegfilgrastim has the same efficacy and safety profile in comparison to Filgrastim. Therefore, since Pegfilgrastim has a easier method of injection and can simplify the HSCT process.